Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1192/s2056474000001380
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychosocial needs of Syrian refugees and the role of Syrian non-governmental organisations

Abstract: Almost 5 million Syrians have been registered as refugees since the conflict started in 2011. Their mental health and psychosocial needs continue to grow as the situation at home gets more complicated. Syrian non-governmental organisations (NGOs) and mental health professionals have been offering their support to help meet these needs. They have set up various centres and teams on the ground that focus their efforts on the most needy individuals. They train and supervise healthcare volunteers, encourage self-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…A study of unaccompanied refugee minors conducted in Sweden showed a significant decrease in PTSD and depression [36]. TRT training for those working with Syrian refugees has taken place in Lebanon and Turkey [37], but no systematic data are available yet for families displaced by the Syrian conflict. Reports on Mental Health and Psychosocial Support (MHPSS) provision for displaced Syrians recommended that programmes such as TRT, which have been validated elsewhere, are promising but require evaluation in the Syrian context [38].…”
Section: The Current Studymentioning
confidence: 99%
“…A study of unaccompanied refugee minors conducted in Sweden showed a significant decrease in PTSD and depression [36]. TRT training for those working with Syrian refugees has taken place in Lebanon and Turkey [37], but no systematic data are available yet for families displaced by the Syrian conflict. Reports on Mental Health and Psychosocial Support (MHPSS) provision for displaced Syrians recommended that programmes such as TRT, which have been validated elsewhere, are promising but require evaluation in the Syrian context [38].…”
Section: The Current Studymentioning
confidence: 99%
“…[6][7][8] Consequently, expatriate Syrian mental health professionals (MHPs), various Syrian non-governmental organisations (NGOs) and international NGOs (INGOs) have made initiatives to provide training and supervision for evidence-based therapies to displaced Syrians. [9][10][11] While doing so mobilises resources, reduces language barriers and enhances cultural sensitivity, it also comes with challenges including high case loads with reduced opportunities for supervision…”
Section: Introductionmentioning
confidence: 99%
“…Many international and local NGOs have contributed to this important work [for reports on some of these initiatives, see (135)(136)(137)]. This includes Syrian NGOs, largely operating from outside the country, such as the Syrian Association for Mental Health, the Union of Syrian Medical Care and Relief Organizations, and the Syrian American Medical Society, as well as charities such as Al-Sham and Balsam (138). Despite these efforts, the need for mental health services in Syria continues to massively outstrip available resources.…”
Section: Syriamentioning
confidence: 99%